Academic Self-Efficacy, Procrastination, and Attrition Intentions - Nemtcan, Efim; Sæle, Rannveig Grøm; Gamst-Klaussen, Thor; Svartdal, Frode (Frontiers in Education, 2022)
Why do students leave universities? The current study addresses the problem of academic attrition from the perspective of students’ intentions. Specifically, we focus on the roles of academic self-efficacy and procrastination in exploring their relationships with attrition intentions. Based on existing research, we expected a negative relationship between academic self-efficacy and attrition intentions, with procrastination as a possible mediator. Furthermore, it was expected that this relationship would differ depending on the type of attrition (i.e., drop-out, transfer university, transfer study field). These hypotheses were investigated among Norwegian students in a questionnaire study (N = 693). Results showed that procrastination partially mediated the relationship between academic self-efficacy and three attrition intentions categories. Although procrastination was a significant mediator of self-efficacy for all types of intentions, the sizes of the direct and indirect effects were different. We conclude that academic procrastination is important in understanding the relationship between students’ self-efficacy beliefs and attrition intentions. Future studies should be cautious when investigating academic attrition and students’ intentions due to their variability.